2018
DOI: 10.25165/j.ijabe.20181103.4162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extrusion conditions on the physicochemical properties of soy protein/gluten composite

Abstract: Soybean protein-gluten blend was extruded using a co-rotating twin-screw extruder. Effects of different extrusion conditions on the textural properties of extrudates were analyzed by central composite design through the evaluation of texturization index, water holding capacity, and hardness of extruded protein products. Extrusion process variables including feed moisture content (40%-60%), screw speed (12-20 Hz), extrusion temperature (120°C-180°C), and gluten content (16%-32%) were studied by the nonlinear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The TI was dependent on the extruder parameters (e.g., type of extruder, screw configuration, rotation speed, barrel temperatures, and feed rate) and feed conditions (e.g., ingredients and moisture content) applied. Numerous studies have investigated the effect of these independent variables on the TI of soy protein-based meat analogs [ 10 , 22 , 23 , 30 , 31 , 32 ]. The TI of the oyster mushroom-soy protein meat analogs ranged from 0.77 to 1.19 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The TI was dependent on the extruder parameters (e.g., type of extruder, screw configuration, rotation speed, barrel temperatures, and feed rate) and feed conditions (e.g., ingredients and moisture content) applied. Numerous studies have investigated the effect of these independent variables on the TI of soy protein-based meat analogs [ 10 , 22 , 23 , 30 , 31 , 32 ]. The TI of the oyster mushroom-soy protein meat analogs ranged from 0.77 to 1.19 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TI of the extrudate achieved the same range of TI (0.7–1.2) as presented by Chen et al and Fang et al on meat analogs made from soy protein without additional ingredients, which were produced by a twin-screw extruder [ 23 , 31 ]. However, several studies have reported a higher range of TI (1.3–1.7) in soy protein-based meat analogs added with wheat gluten and extruded via twin-screw extrusion [ 22 , 30 ]. Figure 3 illustrates the TI of extrudates containing 0%, 7.5%, and 15% oyster mushroom as compared with the TI of hydrated TVP and chicken meat (breast and drumstick).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…104 Currently, soybean protein concentrates and isolates are the benchmark raw materials to 105 produce extruded meat substitutes. Substantial research is performed on soymeal as a raw 106 material (Lin et al, 2002;Wu et al, 2018). Today, three countries account for over 80% of the 107 total soybean cultivation (Karuga, 2018) The configuration at the end of the extruder barrel also affects the properties of the resulting 162 163 design (FKD-2100, DIL e.V., Quakenbrück, Germany).…”
mentioning
confidence: 99%